Readiness of European laboratories for the revised EU Ambient Air Quality Directive: An interlaboratory comparison on levoglucosan, mannosan and galactosan in PM2.5 - Falk Mothes; Laurent Poulain; Jean-Luc Jaffrezo; Sophie Darfeuil; Rhabira Elazzouzi; Karl Espen Yttri; Hans Gundersen; Nicolas Bonnaire; Jean-Eudes Petit; Benjamin Bergmans; Eric Moïs; Theodoros Potouridis; et al. (Atmospheric Environment, 2026)

Inoculation effects on microbial and methane dynamics in daily filled dairy manure storage - Zhenhua Song; Aditya Rawat; Christiane Herrmann; Tina Kabelitz; Qianying Yi; Barbara Amon; David Janke; Tariq Mehmood; Selma Vieira; Jörg Overmann; Thomas Amon (Bioresource Technology, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Investigation of dynamic processes in liquid manure storage in an in vitro system: Implications for methane emissions and modelling - Aditya Rawat; Zhenhua Song; Barbara Amon; Tariq Mehmood; Tina Kabelitz; David Janke; Christiane Herrmann; Jörg Overmann; Selma Vieira; Thomas Amon (Waste Management, 2026)

SIMTEGRAL: A framework for integrating process simulation data in life cycle sustainability assessment studies - Jan-Linus Popien; Abdur-Rahman Ali; Nur Ain Adibah binti Jamaludin; Alexander Barke; Steffen Blömeke; Christoph Herrmann; Thomas S. Spengler (Resources, Conservation and Recycling, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Simulated atmospheric transformation of the tire additives in the aqueous phase: 6-PPD, 6-PPD quinone, diphenylguanidine, and dicyclohexylamine - Volkwin Kuntz; Natalie Kamprad; Bettina Seiwert; Thomas Schaefer; Hartmut Herrmann; Thorsten Reemtsma; Daniel Zahn (Environmental Pollution, 2026)

A fundamental trade‐off among resilience, resistance, efficiency, and redundancy in tidal wetlands - Joshua E. Lerner; Rusty A. Feagin; Thomas P. Huff; Raymond G. Najjar; Astrid Layton; Maria Herrmann; Jose D. Fuentes (Ecology, 2026)
In an era of change, the survival and adaptability of ecosystems will be tested. An optimal ecosystem would be both resistant and resilient to negative disturbance but also efficient and redundant in its growth when given positive subsidies. However, initial evidence has suggested that these properties cannot all be maximized at the same time, and so we sought to quantitatively assess whether there are fundamental trade‐offs between them at the ecosystem level. To achieve this aim, we used a 250‐m resolution NASA MODIS dataset of gross primary productivity (GPP) to monitor 145,871 tidal wetland locations across the conterminous United States every 16 days from March 2000 to December 2020. We quantified the size and duration of the perturbation events in tidal wetland GPP ( n = 13,754,386) and modeled their frequency distributions. Event sizes and recurrence intervals were exponentially distributed and event durations were closely modeled by an inverse power law. This scale‐free manner through which tidal wetlands dissipated perturbations to their GPP flux provided them with long‐term stability across a wide range of geography. We also found that a tidal wetland's positive event responses traded off between properties of efficiency and redundancy, its negative events traded off between resistance and resilience, and that all four properties were orthogonally related to one another. We then constructed a conceptual model to help understand the potential mechanism behind this four‐quadrant trade‐off. The trade‐off appeared to be driven by a feedback between the waiting time and magnitude of positive and negative events, the duration of their effects, and the environmental and physical constraints limiting an ecosystem's growth and productivity. In summary, we detail an emergent pattern of trade‐offs and constraints associated with how tidal wetland ecosystems respond to both positive and negative perturbations in carbon flux.

Multi-element isotope fractionation analysis to investigate the photosensitized reactions of humic substance with 3-chloroaniline - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Herrmann Richnow (Water Research, 2025)

ecoConnect: Integrative carbon management framework for corporations and their products - Johannes Sturm; Thomas Fugger; Frauke Wächter; Christoph Herrmann (Journal of Cleaner Production, 2025)

Multi-element compound-specific stable isotope analysis (2H, 13C, 15N, 33/34S) to characterize the mechanism of sulfate and hydroxyl radical reaction and photolysis of benzothiazole - Haiyan Yu; Limin Ma; Steffen Kümmel; Xiao Liu; Thomas Schaefer; Hartmut Herrmann; Hans-Hermann Richnow (Water Research, 2025)

Determining the key drivers of the potential secondary battery raw materials supply from the urban mine in the European Union - Jana Husmann; Antoine Beylot; Raphael Ginster; Alice Marie; Stéphanie Muller; Audrey Philippe; Daniel Monfort; Steffen Blömeke; Thomas S. Spengler; Christoph Herrmann (Resources, Conservation and Recycling, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Carbon, hydrogen, nitrogen and chlorine isotope fractionation during 3-chloroaniline transformation in aqueous environments by direct photolysis, TiO2 photocatalysis and hydrolysis - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2025)

A structured approach for the compliance analysis of battery systems with regard to the new EU Battery Regulation - Sönke Hansen; Tom Rüther; Mark Mennenga; Christoph Helbig; Gregor Ohnemüller; Filip Vysoudil; Constantin Wolf; Bernd Rosemann; Sandra Pavón; Alexander Michaelis; Thomas Vietor; Frank Döpper; et al. (Resources, Conservation and Recycling, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Circular battery production in the EU: Insights from integrating life cycle assessment into system dynamics modeling on recycled content and environmental impacts - Raphael Ginster; Steffen Blömeke; Jan‐Linus Popien; Christian Scheller; Felipe Cerdas; Christoph Herrmann; Thomas S. Spengler (Journal of Industrial Ecology, 2024)
The European Union (EU) Battery Regulation aims to establish a circular battery production and sets minimum battery material recycled targets for new batteries from post‐production and post‐consumer waste batteries. However, it is uncertain whether these targets can be met due to dynamic market developments and if their compliance results in environmental benefits. Therefore, this study examines the circular battery production in the EU and its impact on material flows and the environment from a market perspective. We combined a system dynamic market model with process models for battery production and recycling, using prospective life cycle assessment. According to our analysis, the projected amount of post‐consumer waste alone may not meet the specified levels of recycled materials due to long battery lifetimes. Thereby, the targets for cobalt are particularly ambitious, with a gap of between 9.8 and 14.6 percentage points for most scenarios. In the case of reduced battery lifetimes, the achievable recycled content across all materials increases by more than 75% in 2032 and by more than 85% in 2037. The avoidance of post‐production waste leads to 9% lower greenhouse gas (GHG) emissions compared to recycling with 100% recycling efficiency. Thus, attributable amounts of post‐production waste and unfavorable prolonged use of batteries create misguided incentives to meet legal targets. Additionally, the delay between production and recycling limits the potential for circular production as this depends significantly on market conditions. Our study highlights, that besides recycling, the industry should especially advance production processes including upstream material extraction and refinement to reduce environmental impacts.

Interlinking environmental and food composition databases: An approach, potential and limitations - Cédric Furrer; Daniel Sieh; Anne-Marie Jank; Grégoire Le Bras; Moritz Herrmann; Alba Reguant-Closa; Thomas Nemecek (Journal of Cleaner Production, 2024)

Estimating energy costs of earthworm burrowing using calorimetry - Elsa M. Arrázola-Vásquez; Mats Larsbo; Yvan Capowiez; Astrid Taylor; Anke M. Herrmann; Thomas Keller (European Journal of Soil Biology, 2024)

Real-world characteristics and use patterns of patients treated with vericiguat: A nationwide longitudinal cohort study in Germany - Fabian Kerwagen; Christoph Ohlmeier; Thomas Evers; Stefan Herrmann; Inga Bayh; Alexander Michel; Silvia Kruppert; Joanna Wilfer; Rolf Wachter; Michael Böhm; Stefan Störk (European Journal of Clinical Pharmacology, 2024)
Purpose Vericiguat reduced clinical endpoints in patients experiencing worsening heart failure in clinical trials, but its implementation outside trials is unclear. Methods This retrospective analysis of longitudinally collected data was based on the IQVIA™ LRx database, which includes ~ 80% of the prescriptions of the 73 million people covered by the German statutory health insurance. Results Between September 2021 and December 2022, vericiguat was initiated in 2916 adult patients. Their mean age was 73 ± 13 years and 28% were women. While approximately 70% were uptitrated beyond 2.5 mg, only 36% reached 10 mg. Median time to up-titration from 2.5 mg to 5 mg was 17 (quartiles: 11–33) days, and from 2.5 to 10 mg 37 (25–64) days, respectively. In 87% of the patients, adherence to vericiguat was high as indicated by a medication possession ratio of ≥ 80%, and 67% of the patients persistently used vericiguat during the first year. Women and older patients reached the maximal dose of 10 mg vericiguat less often and received other substance classes of guideline-recommended therapy (GDMT) less frequently. The proportion of patients receiving four pillars of GDMT increased from 29% before vericiguat initiation to 44% afterwards. Conclusion In a real-world setting, despite higher age than in clinical trials, adherence and persistence of vericiguat appeared satisfactory across age categories. Initiation of vericiguat was associated with intensification of concomitant GDMT. Nevertheless, barriers to vericiguat up-titration and implementation of other GDMT, applying in particular to women and elderly patients, need to be investigated further.

LIFE-Projekt Riverscape Lower Inn - Blühende Inndämme zur Förderung der Biodiversität - Sabine Neuwerth; Thomas Herrmann; Dorothee Hartmann (WASSERWIRTSCHAFT, 2024)

Lithium extraction from geothermal brines: Adsorption-desorption studies on 226Ra (228Ra) and 210Pb on lithium-titanium-oxides (LTO) - Lena Kölbel; Laura Herrmann; Thomas Kölbel; Jochen Schneider (Applied Geochemistry, 2024)

Carbon and hydrogen isotope fractionation of phthalates during photocatalysis reactions in aqueous solution containing Fe(III) complexes or iron minerals - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Oliver J. Lechtenfeld; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2023)

Characteristics of gasification chars – Results from a screening campaign - Annett Pollex; Thomas Zeng; Sabine Bandemer; Axel Ulbricht; Kristina Herrmann; Dieter Bräkow (Biomass and Bioenergy, 2023)

Carbon isotope fractionation of di-(2-ethylhexyl)-phthalate during photosensitized degradation by •OH and S O 4 · - for characterization of reaction mechanisms - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Chemical Engineering Journal, 2023)

Model-parallel Fourier neural operators as learned surrogates for large-scale parametric PDEs - Thomas J. Grady; Rishi Khan; Mathias Louboutin; Ziyi Yin; Philipp A. Witte; Ranveer Chandra; Russell J. Hewett; Felix J. Herrmann (Computers & Geosciences, 2023)

Assessment of the biochemical methane potential of in-house and outdoor stored pig and dairy cow manure by evaluating chemical composition and storage conditions - Julio E. Hilgert; Christiane Herrmann; Søren O. Petersen; Federico Dragoni; Thomas Amon; Vitaly Belik; Christian Ammon; Barbara Amon (Waste Management, 2023)

Lithium extraction from geothermal brines in the Upper Rhine Graben: A case study of potential and current state of the art - Lena Kölbel; Thomas Kölbel; Laura Herrmann; Elif Kaymakci; Iulia Ghergut; Arnaud Poirel; Jochen Schneider (Hydrometallurgy, 2023)

Aqueous-phase photo-oxidation of selected green leaf volatiles initiated by OH radicals: Products and atmospheric implications - Kumar Sarang; Tobias Otto; Sahir Gagan; Krzysztof Rudzinski; Thomas Schaefer; Martin Brüggemann; Irena Grgić; Adam Kubas; Hartmut Herrmann; Rafal Szmigielski (Science of The Total Environment, 2023)

Green batteries for clean skies: Sustainability assessment of lithium‐sulfur all‐solid‐state batteries for electric aircraft - Alexander Barke; Walter Cistjakov; Dominik Steckermeier; Christian Thies; Jan‐Linus Popien; Peter Michalowski; Sofia Pinheiro Melo; Felipe Cerdas; Christoph Herrmann; Ulrike Krewer; Arno Kwade; Thomas S. Spengler (Journal of Industrial Ecology, 2023)
The use of novel battery technologies in short‐haul electric aircraft can support the aviation sector in achieving its goals for a sustainable development. However, the production of the batteries is often associated with adverse environmental and socio‐economic impacts, potentially leading to burden shifting. Therefore, this paper investigates alternative technologies for lithium–sulfur all‐solid‐state batteries (LiS‐ASSBs) in terms of their contribution to the sustainable development goals (SDGs). We propose a new approach that builds on life cycle sustainability assessment and links the relevant impact categories to the related SDGs. The approach is applied to analyze four LiS‐ASSB configurations with different solid electrolytes, designed for maximum specific energy using an electrochemical model. They are compared to a lithium–sulfur battery with a liquid electrolyte as a benchmark. The results of our cradle‐to‐gate analysis reveal that the new LiS‐ASSB technologies generally have a positive contribution to SDG achievement. However, the battery configuration with the best technical characteristics is not the most promising in terms of SDG achievement. Especially variations from the technically optimal cathode thickness can improve the SDG contribution. A sensitivity analysis shows that the results are rather robust against the weighting factors within the SDG quantification method.

The role of wind, mesoscale dynamics, and coastal circulation in the interannual variability of the South Vietnam Upwelling, South China Sea – answers from a high-resolution ocean model - Thai To Duy; Marine Herrmann; Claude Estournel; Patrick Marsaleix; Thomas Duhaut; Long Bui Hong; Ngoc Trinh Bich (Ocean Science, 2022)
The South Vietnam Upwelling (SVU) develops in the South China Sea (SCS) under the influence of southwest monsoon winds. To study the role of small spatiotemporal scales on the SVU functioning and variability, a simulation was performed over 2009–2018 with a high-resolution configuration (1 km at the coast) of the SYMPHONIE model implemented over the western region of the SCS. Its capability to represent ocean dynamics and water masses from daily to interannual scales and from coastal to regional areas is quantitatively demonstrated by comparison with available satellite data and four in situ datasets. The SVU interannual variability is examined for the three development areas already known: the southern (SCU) and northern (NCU) coastal upwelling areas and the offshore upwelling area (OFU). Our high-resolution model, together with in situ observations and high-resolution satellite data, moreover shows for the first time that upwelling develops over the Sunda Shelf off the Mekong Delta (MKU). Our results confirm for the SCU and OFU and show for the MKU the role of the mean summer intensity of wind and cyclonic circulation over the offshore area in driving the interannual variability of the upwelling intensity. They further reveal that other factors contribute to SCU and OFU variability. First, the intraseasonal wind chronology strengthens (in the case of regular wind peaks occurring throughout the summer for SCU or of stronger winds in July–August for OFU) or weakens (in the case of intermittent wind peaks for SCU) the summer average upwelling intensity. Second, the mesoscale circulation influences this intensity (multiple dipole eddies and associated eastward jets developing along the coast enhance the SCU intensity). The NCU interannual variability is less driven by the regional-scale wind (with weaker monsoon favoring stronger NCU) and more by the mesoscale circulation in the NCU area: the NCU is prevented (favored) when alongshore (offshore) currents prevail.

Variability of the Red River Plume in the Gulf of Tonkin as Revealed by Numerical Modeling and Clustering Analysis - Tung Nguyen-Duy; Nadia K. Ayoub; Patrick Marsaleix; Florence Toublanc; Pierre De Mey-Frémaux; Violaine Piton; Marine Herrmann; Thomas Duhaut; Manh Cuong Tran; Thanh Ngo-Duc (Frontiers in Marine Science, 2021)
We study the daily to interannual variability of the Red River plume in the Gulf of Tonkin from numerical simulations at high resolution over 6 years (2011–2016). Compared with observational data, the model results show good performance. To identify the plume, passive tracers are used in order to (1) help distinguish the freshwater coming from different continental sources, including the Red River branches, and (2) avoid the low salinity effect due to precipitation. We first consider the buoyant plume formed by the Red River waters and three other nearby rivers along the Vietnamese coast. We show that the temporal evolution of the surface coverage of the plume is correlated with the runoff (within a lag), but that the runoff only cannot explain the variability of the river plume; other processes, such as winds and tides, are involved. Using a K-means unsupervised machine learning algorithm, the main patterns of the plume and their evolution in time are analyzed and linked to different environmental conditions. In winter, the plume is narrow and sticks along the coast most of the time due to the downcoast current and northeasterly wind. In early summer, the southwesterly monsoon wind makes the plume flow offshore. The plume reaches its highest coverage in September after the peak of runoff. Vertically, the plume thickness also shows seasonal variations. In winter, the plume is narrow and mixed over the whole water depth, while in summer, the plume can be detached both from the bottom and the coast. The plume can deepen offshore in summer, due to strong wind (in May, June) or specifically to a recurrent eddy occurring near 19°N (in August). This first analysis of the variability of the Red River plume can be used to provide a general picture of the transport of materials from the river to the ocean, for example in case of anthropogenic chemical substances leaked to the river. For this purpose, we provide maps of the receiving basins for the different river systems in the Gulf of Tonkin.

Mapping of flowering time, seed quality and clubroot resistance in rutabaga × spring canola populations and their association - Jakir Hasan; Rubeena Shaikh; Swati Megha; David Thomas Herrmann; Berisso Kebede; Habibur Rahman (Euphytica, 2021)

Balance between geographic, soil, and host tree parameters to shape soil microbiomes associated to clonal oak varies across soil zones along a European North–South transect - Jean de Dieu Habiyaremye; Sylvie Herrmann; Thomas Reitz; François Buscot; Kezia Goldmann (Environmental Microbiology, 2021)
Summary Tree root‐associated microbiomes are shaped by geographic, soil physico‐chemical, and host tree parameters. However, their respective impacts on microbiome variations in soils across larger spatial scales remain weakly studied. We out‐planted saplings of oak clone DF159 ( Quercus robur L.) as phytometer in four grassland field sites along a European North–South transect. After four years, we first compared the soil microbiomes of the tree root zone (RZ) and the tree root‐free zone (RFZ). Then, we separately considered the total microbiomes of both zones, besides the microbiome with significant affinity to the RZ and compared their variability along the transect. Variations within the microbiome of the tree RFZ were shaped by geographic and soil physico‐chemical changes, whereby bacteria responded more than fungi. Variations within both microbiomes of the tree RZ depended on the host tree and abiotic parameters. Based on perMANOVA and Mantel correlation tests, impacts of site specificities and geographic distance strongly decreased for the tree RZ affine microbiome. This pattern was more pronounced for fungi than bacteria. Shaping the microbiome of the soil zones in root proximity might be a mechanism mediating the acclimation of oaks to a wide range of environmental conditions across geographic regions.

COR-101, ein menschlicher Antikörper gegen COVID-19 - Stefan Dübel; Andreas Herrmann; Thomas Schirrmann; André Frenzel; Michael Hust (BIOspektrum, 2021)
COR-101 is a fully human, Fc silenced IgG that was discovered by antibody phage display. It reduced the SARS-CoV-2 virus load in the lung by more than 99 percent in Hamster models and led to much faster recovery. Its mode of action has been elucidated by solving the atomic structure of its interaction with SARS-CoV-2. The antibody competes with ACE2 binding by blocking a large area of the SARS-CoV-2 spike protein.

A framework for modelling soil structure dynamics induced by biological activity - Katharina Meurer; Jennie Barron; Claire Chenu; Elsa Coucheney; Matthew Fielding; Paul Hallett; Anke M. Herrmann; Thomas Keller; John Koestel; Mats Larsbo; Elisabet Lewan; Dani Or; et al. (Global Change Biology, 2020)
Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil.

Length Polymorphisms in the Angiotensin I-Converting Enzyme Gene and the Serotonin-Transporter-Linked Polymorphic Region Constitute a Risk Haplotype for Depression in Patients with Coronary Artery Disease - Thomas Meyer; Isabel Rothe; Julia Staab; Hans-Christian Deter; Stella V. Fangauf; Stefanie Hamacher; Martin Hellmich; Jana Jünger; Karl-Heinz Ladwig; Matthias Michal; Katja Petrowski; Joram Ronel; et al. (Biochemical Genetics, 2020)
Genetic variations affecting the course of depressive symptoms in patients with coronary artery disease (CAD) have not yet been well studied. Therefore, we set out to investigate whether distinct haplotypes of the two insertion/deletion polymorphisms in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ) and the angiotensin I-converting enzyme ( ACE ) gene located on chromosome 17 can be identified as risk factors for trajectories of depression. Clinical and genotyping data were derived from 507 depressed CAD patients participating in the randomized, controlled, multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, of whom the majority had an acute cardiac event before study inclusion. Depression scores on the Hospital Anxiety and Depression Scale (HADS) were assessed at baseline and at five follow-up time points up to 2 years after study entrance. At baseline, depression scores did not significantly differ between patients carrying the risk haplotype ACE D/D, 5-HTTLPR I/I ( n = 46) and the non-risk haplotypes ( n = 461, 10.9 ± 2.7 versus 10.4 ± 2.5, p = 0.254). HADS-depression scores declined from study inclusion during the first year irrespective of the genotype. At each follow-up time point, HADS-depression scores were significantly higher in ACE D/D, 5-HTTLPR I/I carriers than in their counterparts. Two years after study inclusion, the mean HADS depression score remained 1.8 points higher in patients with the risk haplotype as compared to subjects not carrying this haplotype (9.9 ± 4.2 versus 8.1 ± 4.0, p = 0.009). In summary, the presence of the ACE D/D, 5-HTTLPR I/I haplotype may be a vulnerability factor for comorbid depressive symptoms in CAD patients.

An endothelial cell line infected by Kaposi’s sarcoma–associated herpes virus (KSHV) allows the investigation of Kaposi’s sarcoma and the validation of novel viral inhibitors in vitro and in vivo - Tatyana Dubich; Anna Lieske; Susann Santag; Guillaume Beauclair; Jessica Rückert; Jennifer Herrmann; Jan Gorges; Guntram Büsche; Uli Kazmaier; Hansjörg Hauser; Marc Stadler; Thomas F. Schulz; et al. (Journal of Molecular Medicine, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Protective potential of dimethyl fumarate in a mouse model of thalamocortical demyelination - Manuela Cerina; Venu Narayanan; Anna Delank; Patrick Meuth; Stephanie Graebenitz; Kerstin Göbel; Alexander M. Herrmann; Stefanie Albrecht; Thiemo Daldrup; Thomas Seidenbecher; Ali Gorji; Tanja Kuhlmann; et al. (Brain Structure and Function, 2018)

The spatial distribution of soil organic carbon in tidal wetland soils of the continental United States - Audra L. Hinson; Rusty A. Feagin; Marian Eriksson; Raymond G. Najjar; Maria Herrmann; Thomas S. Bianchi; Michael Kemp; Jack A. Hutchings; Steve Crooks; Thomas Boutton (Global Change Biology, 2017)
Tidal wetlands contain large reservoirs of carbon in their soils and can sequester carbon dioxide ( CO 2 ) at a greater rate per unit area than nearly any other ecosystem. The spatial distribution of this carbon influences climate and wetland policy. To assist with international accords such as the Paris Climate Agreement, national‐level assessments such as the United States (U.S.) National Greenhouse Gas Inventory, and regional, state, local, and project‐level evaluation of CO 2 sequestration credits, we developed a geodatabase (CoBluCarb) and high‐resolution maps of soil organic carbon ( SOC ) distribution by linking National Wetlands Inventory data with the U.S. Soil Survey Geographic Database. For over 600,000 wetlands, the total carbon stock and organic carbon density was calculated at 5‐cm vertical resolution from 0 to 300 cm of depth. Across the continental United States, there are 1,153–1,359 Tg of SOC in the upper 0–100 cm of soils across a total of 24 945.9 km 2 of tidal wetland area, twice as much carbon as the most recent national estimate. Approximately 75% of this carbon was found in estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. The greatest pool of SOC was found within the Atchafalaya/Vermilion Bay complex in Louisiana, containing about 10% of the U.S. total. The average density across all tidal wetlands was 0.071 g cm −3 across 0–15 cm, 0.055 g cm −3 across 0–100 cm, and 0.040 g cm −3 at the 100 cm depth. There is inherent variability between and within individual wetlands; however, we conclude that it is possible to use standardized values at a range of 0–100 cm of the soil profile, to provide first‐order quantification and to evaluate future changes in carbon stocks in response to environmental perturbations. This Tier 2‐oriented carbon stock assessment provides a scientific method that can be copied by other nations in support of international requirements.

Efficacy of cold fogging and oral herbal extracts on air quality and immune response of broilers - Awad A. Shehata; Klaus Herrmann; Thomas Pfalz; Hafez M. Hafez; Wieland Schrödl; Monika Krüger (Aerobiologia, 2017)

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

Intertemporal choice behavior is constrained by brain structure in healthy participants and pathological gamblers - Bahram Mohammadi; Anke Hammer; Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Manfred Herrmann; Thomas F. Münte (Brain Structure and Function, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

The neural basis of impulsive discounting in pathological gamblers - Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Zheng Ye; Thorsten Fehr; Manfred Herrmann; Thomas F. Münte (Brain Imaging and Behavior, 2015)

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development - Mathieu Latreille; Karolin Herrmanns; Neil Renwick; Thomas Tuschl; Maciej T. Malecki; Mark I. McCarthy; Katharine R. Owen; Thomas Rülicke; Markus Stoffel (Journal of Molecular Medicine, 2015)

Confronting Uncertainty in Life Cycle Assessment Used for Decision Support - Ivan T. Herrmann; Michael Z. Hauschild; Michael D. Sohn; Thomas E. McKone (Journal of Industrial Ecology, 2014)
Summary The aim of this article is to help confront uncertainty in life cycle assessments (LCAs) used for decision support. LCAs offer a quantitative approach to assess environmental effects of products, technologies, and services and are conducted by an LCA practitioner or analyst (AN) to support the decision maker (DM) in making the best possible choice for the environment. At present, some DMs do not trust the LCA to be a reliable decision‐support tool—often because DMs consider the uncertainty of an LCA to be too large. The standard evaluation of uncertainty in LCAs is an ex‐post approach that can be described as a variance simulation based on individual data points used in an LCA. This article develops and proposes a taxonomy for LCAs based on extensive research in the LCA, management, and economic literature. This taxonomy can be used ex ante to support planning and communication between an AN and DM regarding which type of LCA study to employ for the decision context at hand. This taxonomy enables the derivation of an LCA classification matrix to clearly identify and communicate the type of a given LCA. By relating the LCA classification matrix to statistical principles, we can also rank the different types of LCA on an expected inherent uncertainty scale that can be used to confront and address potential uncertainty. However, this article does not attempt to offer a quantitative approach for assessing uncertainty in LCAs used for decision support.

Vγ9 and Vδ2 T cell antigen receptor genes and butyrophilin 3 (BTN3) emerged with placental mammals and are concomitantly preserved in selected species like alpaca (Vicugna pacos) - Mohindar M. Karunakaran; Thomas W. Göbel; Lisa Starick; Lutz Walter; Thomas Herrmann (Immunogenetics, 2014)

Lower thermal capacity limits of the common brown shrimp (Crangon crangon, L.) - Stefan Reiser; Jens-Peter Herrmann; Thomas Neudecker; Axel Temming (Marine Biology, 2014)

Enabling optimization in LCA: from “ad hoc” to “structural” LCA approach—based on a biodiesel well-to-wheel case study - Ivan T. Herrmann; Martin Lundberg-Jensen; Andreas Jørgensen; Thomas Stidsen; Henrik Spliid; Michael Hauschild (The International Journal of Life Cycle Assessment, 2014)

Analyse eines unkonventionellen Vitamin-Transporters - Joanna Ziomkowska; Franziska Kirsch; Andreas Herrmann; Thomas Eitinger (BIOspektrum, 2012)

Obesity is associated with improved survival in patients with organ-confined clear-cell kidney cancer - Sandra Waalkes; Axel S. Merseburger; Mario W. Kramer; Thomas R. W. Herrmann; Gerd Wegener; Julia Rustemeier; Rainer Hofmann; Mark Schrader; Markus A. Kuczyk; Andres J. Schrader (Cancer Causes & Control, 2010)

A GIS based approach to back trajectory analysis for the source apportionment of aerosol constituents and its first application - Dominik van Pinxteren; Erika Brüggemann; Thomas Gnauk; Konrad Müller; Christian Thiel; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2010)

Inefficient clearance of dying cells in patients with SLE: anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kristin Kruse; Christina Janko; Vilma Urbonaviciute; Claudia T. Mierke; Thomas H. Winkler; Reinhard E. Voll; Georg Schett; Luis E. Muñoz; Martin Herrmann (Apoptosis, 2010)

A neurocomputational model for optimal temporal processing - Joachim Haß; Stefan Blaschke; Thomas Rammsayer; J. Michael Herrmann (Journal of Computational Neuroscience, 2008)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Conformational change of influenza virus hemagglutinin is sensitive to ionic concentration - Thomas Korte; Kai Ludwig; Qiang Huang; P. Sivaramakrishna Rachakonda; Andreas Herrmann (European Biophysics Journal, 2007)

Translocation of long chain fatty acids across the plasma membrane – lipid rafts and fatty acid transport proteins - Robert Ehehalt; Joachim Füllekrug; Jürgen Pohl; Axel Ring; Thomas Herrmann; Wolfgang Stremmel (Molecular and Cellular Biochemistry, 2006)

Iron overload in adult Hfe-deficient mice independent of changes in the steady-state expression of the duodenal iron transporters DMT1 and Ireg1/ferroportin - Thomas Herrmann; Martina Muckenthaler; Frank van der Hoeven; Karen Brennan; Sven G. Gehrke; Nadia Hubert; Consolato Sergi; Hermann-Josef Gröne; Iris Kaiser; Isabella Gosch; Martin Volkmann; Hans-Dieter Riedel; et al. (Journal of Molecular Medicine, 2004)

Association analysis of GABA A β2 and γ2 gene polymorphisms with event-related prefrontal activity in man - Georg Winterer; Michael Smolka; Jerzy Samochowiec; Christoph Mulert; Mario Ziller; Richard Mahlberg; Yvonne Wuebben; Jürgen Gallinat; Hans Rommelspacher; Werner Herrmann; Thomas Sander (Human Genetics, 2000)

Lipid domains in the exoplasmic and cytoplasmic leaflet of the human erythrocyte membrane: a spin label approach - Marta Zuvic-Butorac; Peter Müller; Thomas Pomorski; Jeanette Libera; A. Herrmann; Milan Schara (European Biophysics Journal, 1999)

Different manifestations of Toxoplasma gondii infection in F344 and LEW rats - Mirjam-Colette Kempf; Marie-France Cesbron-Delauw; Didier Deslee; U. Groß; Thomas Herrmann; P. Sutton (Medical Microbiology and Immunology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)